Effects of three flavonoids on the metabolism of lenvatinib - Yang, Jinzhao; Chen, Jie; Li, Qingqing; Xu, Ren-ai; Chen, Xiaohai (Frontiers in Pharmacology, 2024)
Lenvatinib is a first-line therapy for the treatment of hepatocellular carcinoma (HCC), an active multi-target tyrosine kinase inhibitor (TKI). The interaction between Traditional Chinese Medicine (TCM) and chemicals has increasingly become a research hotspot. The objective of this study was to pinpoint the effects of three flavonoids on the metabolism of lenvatinib. Enzyme reaction system was established and optimized in vitro, and in vivo experiments were conducted in Sprague-Dawley (SD) rats, where the analytes were detected by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). We found that among three flavonoids, luteolin and myricetin had strong inhibitory effects on lenvatinib metabolism, with half-maximal inhibitory concentration (IC50) values of 11.36 ± 0.46 µM and 11.21 ± 0.81 µM in RLM, respectively, and 6.89 ± 0.43 µM and 12.32 ± 1.21 µM in HLM, respectively. In SD rats, the combined administration of lenvatinib and luteolin obviously expanded the exposure to lenvatinib; however, co-administered with myricetin did not have any changes, which may be due to the poor bioavailability of myricetin in vivo. Furthermore, the inhibitory type of luteolin on lenvatinib showed an un-competitive in RLM and a mixed in HLM. Collectively, flavonoids with liver protection, especially luteolin, may inhibit lenvatinib metabolism in vitro and in vivo.